Effects of N management optimization practices on rice productivity and N loss: a meta-analysis - Liu, Yan; Fu, Zhaopeng; Wang, Weikang; Zhang, Jiayi; Cao, Qiang; Tian, Yongchao; Zhu, Yan; Cao, Weixing; Liu, Xiaojun (Frontiers in Plant Science, 2025)
IntroductionOptimizing nitrogen (N) fertilizer management is key to reducing active N losses in farmland. While current research has proposed various methods to minimize N losses, it often overlooks the need for integrated strategies that address both N losses and crop productivity. By clarifying the impact of different N fertilizer optimization practices on crop productivity and N loss, rational N fertilizer management strategies can be adopted to achieve stable crop yields and reduction in N application rates.MethodsOur study collected 476 peer-reviewed papers and used meta-analysis to analyze the impact of different N optimization management practices (combined application of organic-inorganic fertilizer, deep fertilization, and enhanced-efficiency fertilizer) on yield, N use efficiency, and N loss (N2O emissions, NH3 volatilization, N runoff, and N leaching).ResultsOptimized N management led to a 5%-10% increase in yield, a 17%-21% improvement in N use efficiency, and reductions in N2O (10%-37%), NH3 (7%-40%), N runoff (9%-20%), and N leaching (7%-10%) compared to standard farmer management practices.ConclusionTwice fertilization, the combination of organic and inorganic fertilizers, and the appropriate application of enhanced-efficiency fertilizer could improve rice yield, decrease N losses and ensure food security and improve the sustainable agricultural development.